Dermaptera species in apricot orchards and its pest status in Malatya and Elazi? provinces of Eastern Anatolia, Turkey - Özgen, Inanç; Ayaz, Tarkan; Kitir, Nurgül (Universitatea din Oradea, 2016)
This study was performed for detecting Forficulidae (Dermaptera) species in Malatya and Elazi? apricot orchards, between 2007 and 2011. According to our results, Forficula auricularia L.1758, F. lurida Fischer 1853, F. aetolica (Brunner, 1882), and Isolaboides kosswigi (Burr, 1947) were reported in apricot orchards. A total of 244 specimens was collected from all orchards, belonging to 3 species from Elazi?, and 4 species from Malatya. Amongst recorded species, F. auricularia harms were found in apricot fruits. In these cities, in terms of density and hazardous, F. auricularia was dominant, however it was estimated that after a while F. lurida species would increase its own population. The results of the study; F. lurida, F. aetolica and I. kosswigi were found in their collected fauna for the first time. ©Biharean Biologist, 2016.
Keywords: Apricot; Dermaptera; Fauna; Forficulidae; Pest status